The UN 'Guiding Principles on Business and Human Rights': Methodological Challenges to Assessing the Third Pillar: Access to Effective Remedy. Issue 4 (2nd October 2018) - Lizarazo-Rodríguez, Liliana
ABSTRACT: This article presents methodological challenges for legal analysis when dealing with the third pillar of the United Nations 'Guiding Principles on Business and Human Rights' (UNGP), particularly principles 26, 27 and 31, regarding the state-based non-judicial and judicial mechanisms that provide 'effective' access to an 'effective' remedy. The article reflects on the challenges encountered during a research project whose goal it was to map and evaluate the state-based mechanisms available in Belgium for business-related human rights abuses perpetrated in Belgium or by Belgian businesses in third countries. It is argued that the identification and mapping of the existing state-based mechanisms available to victims of business-related human rights abuses should rely on binding legal sources and therefore, on a precise ex ante legal analysis, whereas the assessment and evaluation of their impact, scope or effectiveness require an ex post empirical analysis.